Pelatihan PELATIHAN AKUNTANSI : PENGARUH TRANSAKSI DALAM JURNAL UMUM DI SMA Tri Ratna - sufiyati, Sufiyati; Andrea, Karen Andrea; Natalia, Natalia (Jurnal Bakti Masyarakat Indonesia, 2023)
Accounting science is used by all fields of business, both large and small companies. Accounting is very useful for all users of financial reports and for all forms of business. During our visit to Tri Ratna High School and based on the results of discussions with the Tri Ratna High School economics teacher regarding economics, class X students had not yet received material on accounting transaction analysis and the effects of transactions in general journals. This material is very important to open Tri Ratna High School students' insight into the influence of accounting transactions in general journals. This material is the first stage in the accounting cycle. By understanding the effects of transactions in a general journal, students can learn more about the accounting cycle and prepare financial reports. The achievement of this training is that class X students at Tri Ratna High School have an understanding of accounting, especially how accounting transactions affect general journals. This training is equipped with a module containing related theory accompanied by examples and practice questions in the hope that students will better understand the material. The next step is to coordinate the training implementation schedule. During the training, students were quite active in discussing and seemed enthusiastic about learning this material. The conclusion obtained is that students can understand the material on the influence of transactions in the journal, reflected in the results of the quiz given after the training and broaden their knowledge/insight regarding accounting science. ABSTRAK Ilmu akuntansi digunakan oleh semua bidang usaha baik perusahaan besar maupun perusahaan kecil. Akuntansi sangat bermanfaat bagi semua pengguna laporan keuangan dan bagi semua bentuk usaha. Dalam kunjungan kami ke SMA Tri Ratna  dan berdasarkan hasil diskusi dengan guru ekonomi SMA Tri Ratna terkait dengan ilmu ekonomi, siswa kelas X belum memperoleh materi analisis transaksi akuntansi dan pengaruh transaksi dalam jurnal umum. Materi ini sangat penting untuk membuka wawasan siswa SMA Tri Ratna bagaimana pengaruh transaksi akuntansi dalam jurnal umum. Materi ini merupakan tahap pertama dalam siklus akuntansi.  Dengan memahami pengaruh transaksi dalam jurnal umum, siswa dapat mempelajari lebih lanjut siklus akuntansi sampai menyusun laporan keuangan. Capaian dari pelatihan ini adalah siswa kelas X SMA Tri Ratna, memiliki pemahaman mengenai akuntansi khususnya bagaimana transaksi akuntansi mempengaruhi jurnal umum. Pelatihan ini dilengkapi dengan modul yang berisi teori terkait disertai dengan contoh dan latihan soal dengan harapan siswa lebih memahami materi.. Langkah berikutnya adalah  melakukan koordinasi untuk jadwal pelaksanaan pelatihan. Dalam pelaksanaan pelatihan, siswa cukup aktif dalam berdiskusi dan terlihat antusias mereka untuk mempelajari materi ini. Kesimpulan yang diperoleh adalah siswa dapat  memahami materi  pengaruh transaksi dalam jurnal, tercermin dari hasil kuis yang diberikan setelah pelatihan dan memperluas pengetahuan/wawasan  mereka mengenai ilmu akuntansi.